High-dose diquat poisoning: a case report. Issue 6 (June 2021) - Huang, Yanxia; Zhang, Renjing; Meng, Mei; Chen, Dechang; Deng, Yunxin
Diquat is a widely used herbicide that is substituted for paraquat. With paraquat off the market, cases of diquat poisoning have been gradually increasing. The kidney is the most frequently impaired organ in diquat poisoning. Few cases of multiple organ failure caused by diquat have been reported. We herein describe a 30-year-old man who orally ingested about 160 mL of enriched diquat. Despite aggressive treatment, the patient's condition progressed to multiple organ failure and death. The pulmonary lesions in this patient were different from those previously reported. This patient did not die of renal failure but of severe respiratory failure. He exhibited three different stages of pulmonary disease. The lung lesions in this case were unique. We hope that doctors will pay more attention to the lung lesions in patients with diquat poisoning in future and find new treatment methods to save the lives of such patients.